Believing in change: Predicting identification, performance, and ethical culture in an organizational acquisition case in Romania - Elana Christina Manole; Petru Lucian Curșeu; Nicoleta Iulia Olar; Oana Căatăalina Fodor (Administrative Sciences, 2024)
This study examines how positive beliefs about organizational changes during a foreign acquisition case influence organizational identification, perceptions of ethical organizational culture, and individual performance seven months post-acquisition. By integrating theories of social identity and organizational change, we offer a new perspective on how positive perceptions of change influence key outcomes following mergers and acquisitions (M&As). Using a cross-lagged design with two cross-sectional datasets within a high-intensity telecommuting organization in Romania, we found that viewing change positively significantly enhanced organizational identification, perceptions of ethical organizational culture, and individual performance. These findings highlight the crucial role of effectively managing the narrative surrounding change processes and enhancing employee perceptions in successful organizational integration following M&As.
Keywords: 350; mergers and acquisitions; attitudes toward change; organizational identification; ethicalorganizational culture; performance; organizational change